The Role of Academic Supervision in Improving the Effectiveness of Inclusive Education Governance - Hasibuan, Zulpan Syarif Supriadi (The Future of Education Journal, 2024)
The aim of this study is to analyze the role of academic supervision in improving the effectiveness of the governance of inclusive education. Supervision in the context of inclusive education is an administrative process and strategic instrument that can enhance the effectiveness of educational management. The focus of this research is on the effectiveness of academic supervision in implementing the governance of inclusive education appropriately. This research uses a literature study method by reviewing literature relevant to academic supervision, inclusive education, and its effectiveness. The results of the literature review explain that effective academic supervision can support the governance of inclusive education, including planning, organizing, implementation, and monitoring, as well as supporting the continuous development of teachers' competencies.